Evaluating Employee Performance through Christian Virtues - Bocarnea, Mihai C. (Christian Faith Perspectives in Leadership and Business, 2018)
In this book the authors create a statistically validated scale measuring the display of each of the nine fruit of the spirit in employees. The authors will discuss how biblical values are applicable to contemporary organizational leadership and management. These nine virtues span a wide breadth of important personal and organizational attributes including benevolence, affection, gladness, relational harmony, tranquility, perseverance, helpfulness, caring for the welfare of others, adherence to the beliefs and value of others, power used soberly, and mastering one's desires. While diverse in nature, the list also suggests a holistic development of personal and organizational character. Understanding the manner in which these traits can be measured will be a significant benefit to HRM and HRD scholars conducting research in Christian servant leadership.